(untitled) (Nigerian Journal of Pharmaceutical Research, 2021)
Background: Tablets must be able to release the active drug in the gastrointestinal tract for absorption. The release profile of solid pharmaceutical dosage formulations can be quantified by assessing the disintegration and dissolution times tests. Binders are adhesives either from sugar or polymeric material that are added to tablet formulations to provide the cohesiveness required for the bonding together of the granules under compaction to form tablets. Objective: The objective of the study was to formulate and assess ibuprofen tablets using different concentrations of binders (Acacia and Gelatin). Methods: The granules were prepared using wet granulation method and analysed for flow properties based on USP/NF protocols. After granule compression, the tablets release profiles were thereafter assessed via the tablet dissolution and disintegration tests. Results: Weight variation, thickness and diameter were within the acceptable values for all batches indicative of a uniform flow. Batches with binder concentrations of 10 % and 20 % failed disintegration test due to a disintegration time above 15 min while the release rate for batches 1 and 4 was about 88 % in 60 min as against the other batches whose release rate was less than 50 % in 60 min as a result of increasing their binder concentrations. Conclusion: The study concluded that increasing the concentration of acacia and gelatin above 5% led to a decrease in percentage of drug released and an increase in disintegration time above 30 mins because 5% batches gave the best release profiles.